A Descriptive Study of Implementation Bring Your Own Device on English Test at the Senior High School Level - Intan Pristi S; Dzulfikri Dzulfikri (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
Bring your own device (BYOD) has become prevalent in education. Students are permitted to use their devices (mobile phones) in the classroom even when they do the test. This article will discuss the students' perception of implementing bring your own device on English test. Besides that, this article will also describe the teacher's policies when the test is in progress to avoid adverse effects such as students cheating during the trial. Keywords: BYOD, mobile phones, test.